PENGARUH SUPERVISI DAN PENDELEGASIAN KEWENANGAN TERHADAP KONFLIK PERAN DAN DAMPAKNYA PADA PRESTASI KERJA PEGAWAI SEKTARIAT DAERAH KABUPATEN ACEH JAYA - Mahrizal Mahrizal (Jurnal Real Riset, 2022)
This study was an empirical study that aimed to determine the effect of supervision and delegation of authority toward the role conflict and its impact on employee job performance of the Regional Secretariat of Aceh Jaya. The research was conducted at the Regional Secretariat of Aceh Jaya District. The study population was all employees of the Regional Secretariat of Aceh Jaya, amounting to 110 people. Due to the size of the population is enough and affordable for the research, thus the population sample was the entire population of the employees. Data was collected through a questionnaire distributed. Primary data were analyzed with path analysis by using SPSS software. Supervision significantly and negatively related to role conflict. Delegation of authority had a positive and significant effect on role conflict. Both supervision and delegation of authority had a positive and significant effect on job performance of employees at the office of the Regional Secretariat of Aceh Jaya. Role conflict became a barrier in mediating role of supervision activities on employee performance at the office of the Regional Secretariat of Aceh Jaya. However, role conflict could play a role in mediating the delegation of authority policy on employees’ job performance.Keywords : Supervision, Delegation of Authority, erole conflict performance of employees